Study on Nanogaphene Particles Cancer Treatment - Hsin-Der Shen (New Frontiers in Medicine and Medical Research Vol. 13, 2021)
Medical researchers at the University of Manchester and the University of Calabria recently found potential use for graphene - as a cancer treatment. After a series of tests on Cancer stem cells (CSC), discovered that graphene oxide (GO) targets and neutralizes these particularly hardy cancer cells. However, we have been researched nanographene particles that also affect the life of cancer cells. Several tests have been undertaken and the experiments of nanographene particles have shown promising results. This study on this treatment was then developed based on the results in applying the appropriate concentrations of nanographene to malignant lymphatic cells and the cancerous lump or mass in skin, breast and neck cancer in vitro to reduce and kill cancer cells. Another purpose of this study is to directly apply this treatment to external cancer areas. These treated cancer areas are shown on the image-guided localization to suppress the cancer cells. And we made these nanographene particles which are charged particles to wreck the growth of the cancer cells.